Necrotic Lip Infection Complicated by Facial Cellulitis and Septic Thoracic Emboli in an 18-year-old Man: A Quiz - Olivier Saraux; Françoise Fabre; Brigitte Milpied; Charles Cazanave; Marie Beylot-Barry (Medical Journals Sweden, 2023)
Abstract is missing (Quiz)